Production and growth of microalgae in urine and wastewater: A review - Siddiqui, Shahida Anusha; Wu, Yuan Seng *; Saikia, Trideep; Ucak, Ilknur; Afreen, Maliha; Shah, Mohd Asif; Ayivi, Raphael D. (Springer, 2023)
Issues of climate change, energy demand, and natural resources depletion are calling for circular methods to produce value-added products such as biomass, biofuel, biofertilizers, and nutraceuticals from waste. For instance, culturing photoautotrophic microalgae in wastewater and urine appears promising to recycle nutrients from waste. Here we review microalgal production with focus on wastewater treatment and urine utilization. We present photobioreactors, parameters influencing algal growth, economical aspects, and limitations from consumer acceptance.